7 - Education for Democracy and Human Rights in African Schools: The Kenyan Experience: 10.4314/ad.v25i1.22114 - Daniel N , Daniel N (Africa Development, 2000)
The increasing clamour for democracy and good governance in Africa risked being futile if a politically literate citizenry remains insignificant and is not proactively dominant in the workings of the state. A democratic culture anchored on the respect and protection of human rights need to be imbibed in wider cross sections of the citizenry. Among the structures in the society that can be used to achieve this objective, the educational systems can be effective in inculcating and fostering a culture of awareness of rights and responsibilities among the populace. But the organizational mode of current formal education systems in Africa, basically Western and trapped in its colonial historic origins in particular, have been lacking in promoting tolerance and democratic values. Rather, the authoritarian school structures have encouraged unquestioning acquiescence to authority. This paper argues that African educators should use the school curriculum to promote democracy and human rights. It stresses changes in the systems and the need to align efforts with a view to ensuring that democratic values would pervade the entire society beginning with organizations and institutions at the grassroots level.